Multiple Dens Invaginatus - A case report and review of literature (Indian Journal of Case Reports, 2016)
Dens invaginatus is a developmental variation of a tooth resulting from an alteration in the normal growth pattern of the dental papilla. It is clinically characterized by a palatine furrow that can be limited to the coronal pulp or may extend to the radicular apex. The commonly affected tooth is maxillary lateral incisor. The occurrence of multiple dens invaginatus is extremely rare. Although a clinical examination may reveal a deep pit or fissure on the lingual surfaces of maxillary anterior teeth, the radiographic examination is the choice for diagnosis of dens invaginatus. Familiarity with the radiographic appearance of this anomaly is essential for the dental practitioner. The purpose of this paper is to present a clinical case of multiple dens invaginatus involving maxillary anterior teeth which was diagnosed during routine radiographic evaluation.